Existo porque resisto: A conversation with LGBTQ+ activists in Xalapa, Veracruz. Issue 2 (May 2023) - Bailey, Emma G
With increased attention toward rights of LGBTQ+ individuals, activists across the globe continue their social and political actions. This article highlights conversation between four activists within their local and state context of Xalapa, Veracruz as a step towards understanding the history and details of LGBTQ+ movements. Following a brief introduction, the conversation is presented in its original Spanish with an English translation.